2016
DOI: 10.1051/0004-6361/201527453
|View full text |Cite
|
Sign up to set email alerts
|

Compositional study of asteroids in the Erigone collisional family using visible spectroscopy at the 10.4 m GTC

Abstract: Two primitive near-Earth asteroids, (101955) Bennu and (162173) Ryugu, will be visited by a spacecraft with the aim of returning samples back to Earth. Since these objects are believed to originate in the inner main belt primitive collisional families (Erigone, Polana, Clarissa, and Sulamitis) or in the background of asteroids outside these families, the characterization of these primitive populations will enhance the scientific return of the missions. The main goal of this work is to shed light on the composi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 46 publications
7
45
1
Order By: Relevance
“…In Fornasier et al (2014), the authors analyze a dataset of over 600 spectra of primitive asteroids in the literature and conclude that the aqueous alteration process is dominant in the 2.1 − 3.1 AU range, at smaller heliocentric distances than proposed by Vilas et al (1994). Morate et al (2016) and Morate et al (in prep. ) shows families in the inner belt with a high amount of hydrated objects.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In Fornasier et al (2014), the authors analyze a dataset of over 600 spectra of primitive asteroids in the literature and conclude that the aqueous alteration process is dominant in the 2.1 − 3.1 AU range, at smaller heliocentric distances than proposed by Vilas et al (1994). Morate et al (2016) and Morate et al (in prep. ) shows families in the inner belt with a high amount of hydrated objects.…”
Section: Discussionmentioning
confidence: 97%
“…We search for the presence of this feature in our sample applying a methodology similar to the one in Carvano et al (2003) and Morate et al (2016). First we calculate the continuum with a linear fit within the 0.55-0.58 and 0.83-0.86 µm intervals.…”
Section: Visible Slopementioning
confidence: 99%
“…The low-albedo X-complex asteroids could be compositionally similar to those of the C-complex (DeMeo et al 2009(DeMeo et al , 2015. An indication of the composition similarities and origin between the low-albedo asteroids belonging to the X-and C-complex also comes from the fact that C-and X-complex asteroids have been found within the same families (Morate et al 2016;Fornasier et al 2016). In the near-infrared survey of Popescu et al (2018) asteroids belonging to the Xcomplex are denoted by the class Xt.…”
Section: Characteristics Of the Spectroscopic X-complexmentioning
confidence: 99%
“…In contrast, Morate et al (2016) found that the distribution of taxonomic classes within the Erigone family ( Figure 5.3) differs significantly from that of Polana-Eulalia. Morate et al (2016) showed that the majority of the Erigone asteroids show a 0.7-µm hydration feature, while the Polana-Eulalias do not. These differences have implications for whether or not hydrated minerals may be present on the surfaces of Bennu, Ryugu, and 2008 EV5, all three of which could come from these two families.…”
Section: Inner Belt Primitive Asteroids: Families and Backgroundmentioning
confidence: 69%
“…FromMorate et al (2016). The different spectral types within the Erigone family, and the percentage of asteroids showing the 0.7-µm hydrated silicate absorption band (blue), for each primitive taxonomic class (green).…”
mentioning
confidence: 99%